Big money [compact disc] - Batiste, Jon, 1986- (Interscope, 2025)
"7x Grammy® winner Jon Batiste returns with a new album, BIG MONEY. An exploration of the real currency of life as we know it today, Batiste melds classic and modern styles of R&B, Americana, soul, roots, jazz, gospel and more to create sounds of jubilee and diasporic expression. The soundtrack of a movement. Social music."--jonbatistestore.com